Halo coupling and cleaning by a space charge resonance in high intensity beams - Ingo Hofmann (Physical Review Special Topics. Accelerators and Beams, 2013)
We show that the difference resonance driven by the space charge pseudo-octupole of high intensity beams not only couples the beam core emittances; it can also lead to emittance exchange in the beam halo, which is of relevance for beam loss in high intensity accelerators. With reference to linear accelerators the “main resonance” k_{z}/k_{x,y}=1 (corresponding to the Montague resonance 2Q_{x}-2Q_{y}=0 in circular accelerators) may lead to such a coupling and transfer of halo between planes. Coupling of transverse halo into the longitudinal plane—or vice versa—can occur even if the core (rms) emittances are exactly or nearly equal. This halo argument justifies additional caution in linac design including consideration of avoiding an equipartitioned design. At the same time, however, this mechanism may also qualify as an active dynamical halo cleaning scheme by coupling a halo from the longitudinal plane into the transverse plane, where local scraping is accessible. We present semianalytical emittance coupling rates and show that previously developed linac stability charts for the core can be extended—using the longitudinal to transverse halo emittance ratio—to indicate additional regions where halo coupling could be of importance.